Right Mini-Thoracotomy for Aortic Plus Mitral with or without Tricuspid Valve Surgery - Faerber, Gloria; Tkebuchava, Sophie; Scherag, André; Bley, Maximilian; Kirov, Hristo; Diab, Mahmoud; Doenst, Torsten (The Thoracic and Cardiovascular Surgeon, 2020)
Objectives Minimally invasive surgery is increasingly performed for isolated aortic or mitral valve procedures. However, combined minimally invasive aortic and mitral valve surgery is rare. We report our initial experience performing multiple valve procedures through a right-sided mini-thoracotomy (RMT) compared with sternotomy.Methods A total of 264 patients underwent aortic and mitral with or without tricuspid valve surgery through RMT (n = 25) or sternotomy (n = 239). Propensity score matching was used for outcome comparisons.Results Of the 264 patients, 25 (age: 72 ± 10 years; 72% male) underwent double (n = 19) and triple valve surgery (n = 6) through RMT and 239 (age: 71 ± 11 years; 54% male) underwent double (n = 176) and triple valve surgery (n = 63) through sternotomy. Sternotomy patients had more co-morbidities and preoperative risk factors (EuroSCORE II 10.25 ± 10.89 vs. RMT 3.58. ± 4.98; p < 0.001). RMT procedures were uneventful without intraoperative complications or conversions to sternotomy. After propensity score matching, surgical procedures were comparable between groups with a higher valve repair rate in RMT. Despite longer cardiopulmonary bypass times in RMT, there was no evidence for differences in 30-day mortality (RMT: n = 2 vs. sternotomy: n = 2) and there were no significant differences in other outcomes. During 5-year follow-up, reoperation was required in sternotomy patients only (n = 2). Follow-up echocardiography showed durable results after valve surgery. RMT patients showed higher survival probability compared with sternotomy, although this difference was not significant (hazard ratio = 0.33; 95% confidence interval: 0.06–1.65; p = 0.18).Conclusion Combined aortic plus mitral with or without tricuspid valve surgery can safely be performed through a RMT with a trend toward better mid-term outcomes.
Keywords: minimally invasive surgery; aortic valve; mitral valve surgery; tricuspid valve